Capital cities at war Paris, London, Berlin 1914-1919. - Winter, J. M.; Robert, Jean-Louis (Studies in the social and cultural history of modern warfare ;, 2007)
This 2007 book is a comparative social and economic history of the capitals of Britain, France and Germany in 1914-18.